Sculptuur in Amsterdam. - Sandberg, Willem (Amsterdam : Stad Amsterdam, 1965)
Appel, Karel ; Badii, Libero ; Calder, Alexander ; Colla, Ettore ; Couzijn, Wessel ; Reinhoud ; Haber, Shamai ; Hoflehner, Rudolf ; Lipchitz, Jacques ; Marini, Marino ; Martin, Etienne ; Moore, Henry ; Perlmuter, Pearl ; Picasso, Pablo ; Schippers, Wim T. ; Szymanski, Rolf ; Tajiri, Shinkichi ; Teschigahara, Sofu ; Tinguely, Jean ; Uhlmann, Hans ; Ultvedt, Per Olof ; Visser, Carel ; Volten, André ; Wotruba, Fritz ; Zadkine, Ossip
biografie
Sculptuur in Amsterdam, 1865 Vondelpark 1965, Amsterdam, 1 apr. - 1 okt. '65
Nederlands & Frans & Engels & Duits
boek